The prevalence, genetic diversity and antibiotic resistance of Staphylococcus aureus in milk, whey, and cheese from artisan farm dairies. (February 2017) - Mehli, Lisbeth; Hoel, Sunniva; Thomassen, Gunn Merethe Bjørge; Jakobsen, Anita Nordeng; Karlsen, Hanne
Abstract: In this study, coagulase positive staphylococci were detected in 45% of the 69 bovine milk, whey and cheese samples taken from five farm dairies, and all raw milk samples were contaminated. Genetic diversity, staphylococcal enterotoxin genes and antimicrobial susceptibility in putative Staphylococcus aureus isolates were investigated. Sixty-one percent of the 72 isolates analysed belonged to the same pulsed field gel electrophoresis group. The spa -typing revealed seven different spa types, t2678 being the most prevalent, but t127 and t197 were also detected. Sixteen different toxin gene profiles were identified in 87.5% of the isolates with sec and tst being the most frequent (52.5%), followed by seg and seh . All isolates were methicillin-sensitive S. aureus, and sensitive to the 12 antibiotics tested. The prevalence of S. aureus and the high diversity of isolates carrying enterotoxin genes constitute grounds for food safety concern in artisanal cheese making, whether pasteurised or not.